2016
DOI: 10.1177/0956462416638224
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis incidence among men who have sex with men in China: results from a meta-analysis

Abstract: Background Recent upsurge of syphilis infections among men who have sex with men (MSM) is one of the major challenges that facing China. However, the overall burden is still not clear. This study aims to summarize the incidence of syphilis among MSM in China by using meta-analysis. Methods We comprehensively searched PubMed-MEDLINE, China National Knowledge Infrastructure (CNKI) and Chinese Wanfang databases. Articles published between December 2009 and March 2015 that met the inclusion criteria were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
(65 reference statements)
4
30
1
3
Order By: Relevance
“…This is consistent with previous studies that found community engagement in sexual health to be associated with increased HIV testing and syphilis testing [35]. This suggests that influencers could be helpful in promoting dual HIV/syphilis testing, given that these related infections often co-occur among MSM in China [39].…”
supporting
confidence: 81%
“…This is consistent with previous studies that found community engagement in sexual health to be associated with increased HIV testing and syphilis testing [35]. This suggests that influencers could be helpful in promoting dual HIV/syphilis testing, given that these related infections often co-occur among MSM in China [39].…”
supporting
confidence: 81%
“…The World Health Organization (WHO) estimates there are 18 million cases worldwide, with 5.6 million new cases each year (2). Although syphilis rates are highest in low-and middle-income regions (3), higher-income settings, including Canada (4), Europe (5,6), United Kingdom (7,8), China (2,(9)(10)(11), and the United States (12,13) are experiencing increasing syphilis rates. Of utmost concern is the increasing occurrence of congenital syphilis, which causes adverse pregnancy outcomes, including stillbirth, early neonatal death, and preterm birth (14).…”
mentioning
confidence: 99%
“…5 A recent metaanalysis from China shows increasing incidence of Syphilis in MSM population which in turn may lead to higher rates of spread of other sexually transmitted infections (STIs) including HIV. 6 In our study, 9.9% of the MSM had latent syphilis as indicated by VDRL and or TPHA reactivity. Increased incidence may be due to decreased use of condoms, the introduction of antiretroviral therapy free of cost which has resulted in loss of fear of acquiring and transmitting HIV and resurgence of gonorrhoea and syphilis and asymptomatic nature of the disease.…”
Section: Methodsmentioning
confidence: 99%